, Expression Of Serum Inflammatory Factors And Vascular Endothelial Growth Factor And Volume Reduction Rate in Thyroid Nodules Treated With Ultrasound-Guided Radiofrequency Ablation: Serum Inflammatory Factors And Vascular Endothelial Growth Factor - Jin, Huijuan (Journal of Medical Biochemistry, 2026)
Background: The incidence of benign thyroid nodules (TN) is high. Minimally invasive ablation is a commonly used treatment in clinical practice. However, the distinctions in efficacy and safety between different ablation techniquesstill need to beclarified.Objectives: It aimed to compare the effects of ultrasound-guided radiofrequency ablation (RFA) and microwave ablation (MWA) in benign TN.Methods: 103 patients with benign TN were retrospectively included and allocated toa RFA group (n = 58) or a MWA group (n = 45). Baseline data and serum levels of inflammatory factors, nodule volume, and vascular endothelial growth factor (VEGF) expression in nodule tissues pre- and post-surgery were extracted.Results: No distinctions in baseline data were noted (P > 0.05). On day 1 after surgery, the levels of inflammatory factors were lower in the RFA group versus the MWA group; The volume reduction rate of the RFA group was higher at each time point after surgery; At 6 months after surgery, the RFA group had a lower rate of VEGF-positive cells and a higher proportion of negative + weakly positive cells (P < 0.05). The RFA group had a superiorresponse rate (94.83% vs. 77.78% in the MWA group), and a lowerincidence of adverse reactions (ARs)(13.79%), with faster recovery (P < 0.05).Conclusion: Ultrasound-guided RFA for benign TN is superior in reducing inflammatory stress, promoting nodule shrinkage, and inhibiting VEGF expression.